Photoperiodic cues regulate phenological carry‐over effects in an herbivorous insect. (7th September 2017) - Salis, Lucia; van den Hoorn, Erik; Beersma, Domien G. M.; Hut, Roelof A.; Visser, Marcel E.
Abstract: To maximise their fitness, organisms need to synchronise their phenology with the seasonal variation in environmental conditions. Most phenological traits are affected by environmental abiotic cues such as photoperiod, temperature and rainfall. When individuals with complex life cycles fail to match one of the stages with the favourable environment, the negative conditions experienced may lead to carry‐over effects and, thus, influence fitness in subsequent stages. In the winter moth, an herbivorous insect with an annual life cycle, timing of egg‐hatching in spring is strongly influenced by temperature and varies from year to year. To investigate whether the phenological variation in egg‐hatching date affects subsequent stages, we analysed data on egg‐hatching date and adult catching date (considered here to be a proxy for adult eclosion date) from our long‐term study (1994–2014). Furthermore, we experimentally manipulated the photoperiod experienced by newly hatched larvae and recorded the phenology of their subsequent life cycle stages. In the long‐term field study, we found that the timing of winter moth egg‐hatching in spring varied strongly from year to year. Interestingly, however, the timing of adult eclosion date in winter showed little inter‐annual variation. In line with these findings, our experimental data showed that the winter moth shortened the duration of their pupal development when they experienced a late spring photoperiod as a larva, and prolonged pupal development when experiencing early spring photoperiod. The effects of the larval photoperiodic treatments persisted during egg development in the following generation. The results show that a phenological shift that occurs during an early life stage is partially compensated during subsequent stages and suggest that the mechanism underlying this compensation is mediated by photoperiod. Winter moths regulated their phenology in such a way that the variation in the egg‐hatching stage was not carried over to the next life cycle stages. This has strong effects on fitness as it (1) ensures the synchronisation of adult eclosion during the mating period and (2) is likely to reduce potentially negative fitness consequences of phenological mismatches in egg‐hatching in the following generation. Overall, these findings stress the importance of understanding phenological carry‐over effects to forecast the impact of global change in species with complex life cycles. Aplain language summary is available for this article. Abstract : Plain Language Summary